DETERMINAN PENGUNGKAPAN CSR DAN LEGITIMASI PERBANKAN SYARIAH - Jahja, Adi Susilo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
The existence of organisation can be determined by its legitimacy. Legitimacy theory stated that the organisation should in line with the values and norms of its stakeholders.Â Indonesia Islamic banking legitimacy is important since this industry in Indonesia is still have small market share, but Indonesia Financial Authority (OJK) has commitment to enhance the contribution of this industry to the Indonesian development. Conceptually, legitimacy could be hanced by Corporate Social Responsibility (CSR) disclosure, while CSR disclosure is determined by company visibility, profitability, company size, and ownership structure.